Air pollution in Jalalabad city: its causes, effects, and solutions - Hemat, Toryalai; Sekandary, Muhammad Ibrahim; Hadi, Fazlullah; Sadiq, Abdul Saboor (Eximia, 2022)
Air pollution refers to any physical, chemical, or biological changes in the composition of air that are detrimental to the life and health of living organisms. These changes have various factors, such as the increase of dust, gases, smoke and other undesirable substances. Air pollution has two types of causes. Natural causes and non-natural causes. The non-natural causes are caused by humans, and they include everything from food and drink to work and housing. The importance of the research study lies in the fact that the causes of air pollution in Jalalabad city have been identified and necessary solutions have been proposed. Furthermore, this issue is very critical and important in terms of protecting human life and health. The purpose of the research is to reveal the causes, effects, and solutions to air pollution. On the one hand, it has been made easier for the officials to take positive and effective measures to solve the matter. On the other hand, the public's responsibilities have also been laid out. As a result of the current work, the level of pollution in the air in Jalalabad city will go down. The research methodology is both qualitative and quantitative. The first part of the research is library research in which the most reputable and trustworthy published materials such as books, scholarly articles, and credible internet sites are used. The second part of the research is field research. For this part, questionnaires are used to gather information, which is then analyzed with SPSS software. As a result of the research study, it has been revealed that the level of air pollution in Jalalabad city is high and the main reasons are the lack of a regular transportation system, the abundance of garbage, the lack of attention of the officials, and the people's non-observance of urban cultural principles. Due to these factors, people experience various problems and diseases in society. The gathered information shows that the prevention of the problem can be done with the construction of a regular sewerage system for the city of Jalalabad, the attention of the citizens to urban culture and regular traffic management.